Le istituzioni educative nella Costituzione italiana (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Ricognizione costituzionale del fenomeno educativo - 2. L’educazione familiare - 3. L’educazione scolastica - 4. L’educazione religiosa.Educational Institutions in the Italian ConstitutionABSTRACT: According to the current Constitution, Italy presents itself as a pluralist and participatory democracy, in which certain functions aimed at enhancing the human person are not taken directly by the State – except in exceptional cases in which the public authorities intervene, for reasons of necessity, in a subsidiary or supplementary way – but they are normally assigned to specific social subjects (or formations), among which the educational institutions have a special and qualified position. The present contribution intends to highlight that the Italian “social State” does not present itself as a “educating State” in its own educational models that the public structures impose in an authoritarian way on the single components of the national collectivity. On the other hand, the Italian Constitution, in recognizing social relevance to the educational function, assigns its concrete management to certain “"pedagogical agencies” or “educational institutions” operating autonomously within the civil society: among which the qualified family holds a qualified position. School and religious confessions. They do not operate in the name or on behalf of the State, but operate within a framework of legal, cultural and institutional guarantees and pluralism, within a normative framework dictated in this regard by the constitutional text and by ordinary legislation. By carrying out the special role assigned to them by the Italian legal system, educational institutions participate in the democratic dynamics of the country, contributing with their work to the construction and evolution of the civil and national community.
Keywords: Istruzione pubblica e IRC